2020
DOI: 10.1038/s41598-020-70279-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation into the effect of carbon nanotubes interaction with CO2 in molecular separation using microporous polymeric membranes

Abstract: The use of nanofluids has been recently of great interest to separate acidic contaminants such as CO 2. The main objective of this research is to assess the influence of carbon nanotubes (CNTs) addition to distilled water on enhancing the CO 2 molecular separation through a porous membrane contactor (PMC). For this aim, a comprehensive model is developed based on non-wetted and counter-current operational modes to evaluate the principal mass and momentum transport equations in tube, membrane and shell compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…To solve PDEs of mass and momentum, COMSOL Multiphysics version 6 was installed on a 64-bit platform with an Intel(R) core (TM) i7-10510U CPU and a 16 Gigabyte RAM. The needed time for solving the PDEs and present the results was about 20 s. Moreover, with the aim of managing the material balance error during the solution of mass/momentum PDEs, PARDISO numerical solver was employed owing to its brilliant advantages like excellent memory performance and robustness 58 , 59 . The principal PDEs of mass and momentum in tube, membrane and shell sides are presented in Table 2 .…”
Section: Modelingmentioning
confidence: 99%
“…To solve PDEs of mass and momentum, COMSOL Multiphysics version 6 was installed on a 64-bit platform with an Intel(R) core (TM) i7-10510U CPU and a 16 Gigabyte RAM. The needed time for solving the PDEs and present the results was about 20 s. Moreover, with the aim of managing the material balance error during the solution of mass/momentum PDEs, PARDISO numerical solver was employed owing to its brilliant advantages like excellent memory performance and robustness 58 , 59 . The principal PDEs of mass and momentum in tube, membrane and shell sides are presented in Table 2 .…”
Section: Modelingmentioning
confidence: 99%
“…For solving the governing equations of MDEA-based solvent and gas phase, a finite element method is employed via COMSOL Multiphysics 5.4. The adaptive meshing and error control were employed, and PARDISO solver as one of the effective solvers for simulating membrane systems was employed to minimize the calculations errors 35 , 36 . It was found that the numerical solution time for solving the governing mass and momentum equations was about 3 min.…”
Section: Model Developmentmentioning
confidence: 99%